An Analysis of High School Explainer Videos for English Learning Through the Lens of Cognitive Theory of Multimedia Learning (CTML) - La Ode Muhammad Nur Rahim; Deddy Amrand; Mursalim Mursalim (Journal of Language Education and Educational Technology (JLEET), 2023)
This research aims to assess the alignment of high school explainer videos for English learning with the Cognitive Theory of Multimedia Learning (CTML) principles and identify contributing factors to the alignment. The research Employed a content analysis design using descriptive analysis techniques. An analytic rubric, adapted and developed based on CTML principles, was utilized for evaluating the alignment of explainer videos. The research focused on four cases of explainer videos targeting high school students to teach English writing skills using a genre-based approach. Results indicate a majority of alignment with CTML principles, predominantly falling within a high to moderate alignment range. The notable contributing factors to positive alignment trends are attributed to the compatibility of the three key facets: explainer video characteristics, the systematic nature of writing skills in a genre-based approach and the CTML’s principles. Conversely, the primary contributing factors to negative alignment trends stem from the perplexity of balancing time constraints while needing to meet the standards of educational multimedia, coupled with the demand to informatively deliver complex content, especially in the context of writing. Furthermore, the main contributing factors to the emergence of variations in both alignment and misalignment are inclined to associated with expertise of explainer video creators in educational multimedia design, subject matter and individual preferences.